Translation Shifts in Gibran's The Prophet - Abdul-Kawi Hizam; Mohammed Abduh Nagi Ali Khoshafah; Abdulrahman Ahmed Mohammed Noaman; Zubaida Mohammed Al-Hazmi (Taez University, 2024)
This research paper aimed at investigating translation shifts in two Arabic translations of Gibran's The Prophet, using Leuven-Zwart's comparative and descriptive model. The main objective of this paper was to identify the micro structural shifts that induced shifts on the macro structural level and to analyze their consequences on the general meaning of the original text with an attempt to explore the potential factors behind them. In this respect, it followed an analytical, descriptive and comparative methodology, analyzing (23) examples taken from the source text (ST) and its target texts (TTs). In spite of the relatively limited sample, it offered valuable insights into the crucial importance of having sufficient knowledge about the author's philosophy, high proficiency in the TL, and adequate determination of translation purpose upon the original text's purpose. The findings revealed, through many occasions, that unlike Naimy, Bashir's having no close friendship with Gibran and also no appropriate competency in the target language (TL) led him making big macro shifts. Most importantly, the findings also confirmed in some occasions that they both took the translation purpose differently with a view to create an impact on determined target readers and thus adversely affecting the macro message and purpose of the original text as a whole.